Spatial Function Diversification: A Case Study of Medical Care Institutions - Lv, Mou; Liu, Lianya (Transactions on Social Science, Education and Humanities Research, 2024)
With the continuous improvement of living levels, people’s health needs and psychological needs are getting higher and higher. the functional needs of living conditions and lifestyles are becoming more and more refined, so that the design of diversified spatial functions has emerged. In a limited space, the diversified design is rich in functions, efficient and coordinated, and has the characteristics of adaptability, richness, harmony, unity and intensification of multiple orders. This article explores the human activities, time dimensions and space dimensions in the design of diversified spatial functions. Taking the medical care institution—postpartum rehabilitation center as an example, the design reflects the diversified characteristics of spatial functions.